Biodegradable Ethylene‐Bis(Propyl)Disulfide‐Based Periodic Mesoporous Organosilica Nanorods and Nanospheres for Efficient In‐Vitro Drug Delivery. (17th July 2014) - Croissant, Jonas; Cattoën, Xavier; Man, Michel Wong Chi; Gallud, Audrey; Raehm, Laurence; Trens, Philippe; Maynadier, Marie; Durand, Jean‐Olivier
<x xml:space="preserve">Abstract</x> Periodic mesoporous organosilica nanorods and nanospheres are synthesized from 1, 4‐bis(triethoxysilyl)ethylene and bis(3‐ethoxysilylpropyl)disulfide. The nanosystems present the long‐range order of the hexagonal nanostructure. They are degraded in simulated physiological conditions. The loading and release of doxorubicin with these nanosystems are both pH dependent. These nanoparticles are endocytosed by breast cancer cells and are very efficient for doxorubicin delivery in these cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>